Development and characterization of osteogenic cell sheets in an in vivo model - Pirraco, R. P. (2008)
[Excerpt] Despite some successes in the tissue engineering field its evolution seems to be tampered by limitations such as cell sourcing and the lack of adequate scaffolds to support cell growth and differentiation. The use of stem cells combined with cell sheet engineering technology seems a promising way to overcome these limitations. In this work bone marrow cells were flushed from 3 weeks old Wistar rat femurs and cultured in basal DMEM medium until subconfluence. Cells were then transferred to thermo-responsive dishes (3 x10⁵ cells/dish) and cultured for 3 weeks in osteogenic medium. [...]